2002
DOI: 10.3354/dao051013
|View full text |Cite
|
Sign up to set email alerts
|

An Aeromonas salmonicida type IV pilin is required for virulence in rainbow trout Oncorhynchus mykiss

Abstract: Aeromonas salmonicida expresses a large number of proven and suspected virulence factors including bacterial surface proteins, extracellular degradative enzymes, and toxins. We report the isolation and characterization of a 4-gene cluster, tapABCD, from virulent A. salmonicida A450 that encodes proteins homologous to components required for type IV pilus biogenesis. One gene, tapA, encodes a protein with high homology to type IV pilus subunit proteins from many Gramnegative bacterial pathogens, including Aerom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 63 publications
0
47
0
Order By: Relevance
“…It has for example been reported that the Aeromonas salmonicida PilA homologue, TapA, was required for virulence in rainbow trout (Oncorhynchus mykiss (Walbaum)) and Atlantic salmon (Salmo salar L.) [11,14]. In addition, the pilA-encoded type IV pilus of V. vulnificus contributed significantly to the persistence in Crassostrea virginica oysters [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has for example been reported that the Aeromonas salmonicida PilA homologue, TapA, was required for virulence in rainbow trout (Oncorhynchus mykiss (Walbaum)) and Atlantic salmon (Salmo salar L.) [11,14]. In addition, the pilA-encoded type IV pilus of V. vulnificus contributed significantly to the persistence in Crassostrea virginica oysters [13].…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on the major pilin, PilA, considerable homology to the type IV pilin precursor proteins of many other bacteria was observed [11,26,28,35,36]. Typically, the N-terminal region of the premature PilA of V. anguillarum VIB15 is dominated by a short, hydrophilic leader peptide and shows the presence of the conserved consensus cleavage site with the GFTLIE amino acid motif, which is identical in PilA of several other Vibrio species such as V. cholerae [26].…”
Section: Both Vib15rifmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo experiments in rainbow trout (Oncorhynchus mykiss) showed that the Tap pilus contributes moderately to virulence. A tapA mutant constructed by allelic exchange was found to be slightly less pathogenic than wild type when delivered by intraperitoneal injection (Masada et al, 2002). Boyd et al (2008) showed that the Tap pilus also made a moderate contribution to virulence in Atlantic salmon (Salmo salar), while the Flp pilus made little or no contribution.…”
Section: Adhesinsmentioning
confidence: 99%
“…It is located on the surface of many Gram-negative and Gram-positive bacteria, at one or both poles [18][19][20]. And also, it is involved in surface adhesion and colonization [21][22][23], tropism determination [24], biofilm formation [23], genetic material uptake [21] and virulence of bacteria [25][26][27]. Fimbriae expression is controlled by transcriptional and post-transcriptional [28] and is influenced by several factors: bacterial growth rate [29], culture medium composition [30,31], temperature [32], pH and osmolarity [33].…”
Section: Introductionmentioning
confidence: 99%